Numerical simulation of dissimilar metal welding and its verification for determination of residual stresses (Fracture and Structural Integrity, 2016)
This paper summarizes the results of the through-thickness residual stress distributions on dissimilar metal weld (DMW) mock-up. DMWs, as welded joints between ferritic steels and either austenitic stainless steels or nickel-based alloys, are commonly found in piping systems of NPPs as well as in other industrial plants. The welding of the mock-up is simulated by the 3D finite element model using temperature and phase dependent material properties. The commercial finite element code MSC.Marc is used to obtain the numerical results by implementing the Goldak’s double ellipsoidal shaped weld heat source and combined convection radiation boundary conditions. Residual stress measurements are performed on welded joints to validate the simulation results. The validated residual stress distributions can be used for the life time assessment and failure mode predictions of the welded joints.
Keywords: Dissimilar metal welding; Finite element analysis; Residual stress; Phase transformation